2007
DOI: 10.1016/j.jneuroim.2007.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential ex vivo nitric oxide production by acutely isolated neonatal and adult microglia

Abstract: Microglia are the macrophage population residing in the parenchyma of the central nervous system (CNS), and are thought to play critical roles in CNS development, homeostasis and defense against pathogens. Microglia are capable of rapidly responding to microbial pathogens through engagement of their Toll-like receptors (TLRs). We first compared the efficiency of these responses in primary microglia acutely isolated from adult and neonatal mice. While the cytokine and chemokine responses of adult microglia were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…6C). hsp70 is a known ligand of TLR2 and TLR4, where extracellular hsp70 activates microglia and stimulates proinflammatory cytokine gene expression through NF-B (16,51). The ability of hsp70 to induce IFN-␤ has not previously been addressed, although other TLR4 ligands (e.g., LPS) are capable of IFN-␤ induction, requiring signaling through IRF3 (44).…”
Section: Resultsmentioning
confidence: 99%
“…6C). hsp70 is a known ligand of TLR2 and TLR4, where extracellular hsp70 activates microglia and stimulates proinflammatory cytokine gene expression through NF-B (16,51). The ability of hsp70 to induce IFN-␤ has not previously been addressed, although other TLR4 ligands (e.g., LPS) are capable of IFN-␤ induction, requiring signaling through IRF3 (44).…”
Section: Resultsmentioning
confidence: 99%
“…TLR2 and -4 are unique in that they recognize extracellular endogenous ligands, such as heat shock proteins, and extracellular hsp70 is known to activate microglia/macrophages predominantly through TLR4 but also through TLR2 (21). Stimulation of TLR4 by hsp70 results in secretion of IFN-␥, nitric oxide, tumor necrosis factor alpha, interleukin 1␤, interleukin 6, CCL2 to -5, and CXCL1 (5,46,49). In order to engage these TLRs, hsp70 would need to be released from cells, and this could occur either through secretory mechanisms or following cell death due to viral CPE.…”
Section: Discussionmentioning
confidence: 99%
“…For example, microglia in neonatal brain are morphologically and functionally different to microglia in the healthy adult brain (Brannan and Roberts, 2004). Also, it has been shown that there is a differential ex vivo nitric oxide production by acutely isolated neonatal and adult microglia (Schell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%